The Influence of narrowcasting in the programming and management of DWNU 107.5 a case study - Gahol, Carlo Roman L.
This case study was conducted to assess the influence of impact of narrowcasting in the management and programming of an FM radio station. Narrowcasting or niche programming is a type of programming strategy that specifically targets a particular type of audience. Rather than attempting to reach a broad, wider audience, as is the general practice of most stations, narrowcasting caters to a small, special clientele. The station adopts a unique programming format that appeals to its targeted listeners in its efforts to find its own special niche in the highly competitive field of commercial broadcasting. This study focused on the station DWNU 107.5, the only radio station the FM band catering to a select audience of rock listeners. The station's history showing the development of its programming from its initial New Wave format to the present Modern Rock. The study also looked into some of the station's programs and special events such as the Annual NU 107 Rock Awards to find out the extent of influence of narrowcasting. How narrowcasting was implemented in the management policies of hiring personnel and choosing the advertisements it aired was also analyzed. The researcher conducted interviews, monitored specific programs, and utilized written materials on NU 107 to gather the necessary data. The results showed that narrowcasting exerted a strong influence on the programming and management of the station. There was a conscious effort on the part of management and staff to project, maintain and preserve its image as the only rock station in Metro Manila with a special select listenership. The rock format served as the basis for all its programs from the songs played, to special affairs hosted, particularly the Annual NU Rock Awards, a much awaited event among rock bands and aficionados. The management policies and guidelines concerning the selection of personnel and advertisements aired were also dictated by narrowcasting. The management and staff, particularly the announcers/disc jockeys are also rock enthusiasts. The products and the advertisements presented and aired in the station are selected to conform and complement with the image of the rock station. The decision to go into narrowcasting and to be different from the rest of the stations proved to be sound. The only rock station that has survived through the years, DWNU 107.5 has found a niche among rock listeners, filling their needs and meeting their demands. The fact the NU 107 has achieve considerable success in narrowcasting implies that there is an audience for new, alternative programming formats. Its success can inspire and perhaps encourage and embolden other radio stations to take the risk and experiment new formats, and in the process, find their own niches in commercial radio broadcasting.